Taxonomic and phylogenetic overview of the genus Volvariella (Volvariellaceae), with a focus on European species - Caballero, Fernando; Justo, Alfredo; Parra, Luis A.; Angelini, Claudio; Consiglio, Giovanni; Dovana, Francesco; Ferisin, Giuliano; Kaygusuz, Oğuzhan; Knudsen, Henning; Llimona, Xavier; Muñoz, Guillermo; Daniëls, Pablo P.; et al. (Phytotaxa, 2025)
We present a comprehensive nrITS phylogeny of the genus Volvariella, with a focus on European species. Detailed descriptions and nomenclatural and taxonomic comments are provided for fourteen Volvariella species originally described from Europe (V. bombycina, V. caesiotincta, V. clavocystidiata, V. dunensis, V. hypopithys, V. latispora, V. murinella, V. pusilla, V. reidii, V. strangulata, V. surrecta, V. taylorii, V. terrea, and V. volvacea). Fourteen European species are described as new: V. cordispora, V. cryptica, V. deceptiva, V. glaucocephala, V. globifera, V. graminicola, V. izmirensis, V. mediterranea, V. neoparvula, V. nodosicystis, V. pilosipilea, V. ranulicystis, V. siquieri, and V. sylvipraticola. Full descriptions and illustrations are provided for all species.